Residents’ Perception and Assessment of Geomorphosites of the Alvão—Chaves Region - Martins, Bruno Manuel dos Santos de Castro (2018)
This work focuses on the paradigms of a multidimensional and interdisciplinary evaluation of geomorphological heritage and its valorisation within a geosystemic reading of relations between a geomorphological and cultural landscape. This research aims to (i) select geomorphosites at different scales, which represent the regional geodiversity, according to an interdisciplinary approach; and (ii) better understand the perception of the local population concerning the different values of geomorphosites by applying a questionnaire that addresses the scientific, preservation, use, cultural, and educational dimensions. First, the authors selected the geomorphosites at a regional level by respecting the following criteria: (i) representativeness of the landform as a morphogenetic process; (ii) the witnessed periods of morpho-dynamics with potential to contribute to the reconstruction of paleoenvironmental conditions; (iii) the current morpho-dynamic nature; (iv) the importance to the shaping of the cultural landscape; and (v) the use value. Results showed that the major landforms are perceived as those with greater value by the local populations.